MONITOR THE USE OF ANTIBIOTICS IN INTENSIVE CARE UNITS WITH SPECIAL FOCUS ON RESTRICTED ANTIBIOTICS IN TERTIARY CARE HOSPITAL OF INDIA - Singh, Abhishek Pratap; Gupta, Dr. Usha; Das, Saumya (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The present study was to monitor the use of antibiotics with restricted antibiotics in intensive care units (ICUs). The aim of this study was to observe number of patients receiving antibiotic(s), to observe number of patient receiving restricted antibiotics(s), number of restricted antibiotic(s) forms filled in 48 hrs, observing number of instances where within three or more than three antibiotics given for more than 3 days, any adverse drug reaction and medication error related in ICUs. Methods: The study was done prospectively in ICUs of a tertiary care hospital. 200 patients were selected from ICUs on a random basis. The duration study was 6.5 months. All adult patients admitted in ICUs who received an antibiotic therapy within 24 hrs of admission were included. Outpatient department patients and patient admitted in the wards were not included in the study. Results: Among 200 patients, the total number of patients received antibiotic were 188 (94%), while 12 (6%) patients were not received. Among 188 patients, 51 patients received restricted antibiotics, i.e., 27.2% and 137 patients not received restricted antibiotic, i.e. 72.8%. Out of 188 patients received antibiotics including restricted antibiotics only 31 patients received three or more than three antibiotics for three or more than three days, which are 16.4% and 157 patients, not received three or more than three antibiotics for three or more than three days which were 83.6%. According to Antimicrobial Stewardship Program, physician prescribed restricted antibiotic must have to fill restricted antimicrobial form, among 51 patients, only 8 (15.6%) forms were received. Keywords: Antibiotics, Restricted antibiotics, Outpatient department, Antimicrobial stewardship program, Intensive care units.